Pediatric robotic and reconstructive urology a comprehensive guide - Gundeti, Mohan S. (Wiley-Blackwell, 2012)
The most exciting contemporary developments in pediatric urology are now demonstrated in text and on video in this innovative, practical guide. A practical text for experienced practitioners and trainees alike, this comprehensive resource introduces the new techniques and surgical planning required to begin mastery of robotic approaches.